CONCEPTUAL FRAMEWORK FOR ENVIRONMENTAL RATING SYSTEMS FOR INFRASTRUCTURE PROJECTS IN SRI LANKA: APPLICATION TO SMALL HYDROPOWER PROJECTS - JAYAWICKRAMA PIHILI ANGE GEDARA THILINI SHIROMANI (2014)
Ph.D